Supervisi Dalam Pendidikan Islam - Nuri Rahmadani (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Educational institutions in Indonesia are sheltered and controlled by two ministries where public schools are controlled by the Ministry of National Education while religious schools, in this case madrasas are controlled by the Ministry of Religion. However, this educational institution will always receive supervision where the supervisory public schools are from the Ministry of Education except for the PAI teacher and the Madrasah supervisors from the Ministry of Religion. The effective functioning of an educational institution both public education and religious education or Madrasa can not be separated from the active role of a supervisor, because in fact the supervisor will always control the course of education in the school or madrasa institution with a careful session. All forms of oversight carried out aim that an education that takes place at educational institutions runs according to the direction and objectives of the education curriculum both locally and nationally. All supervision activities carried out by a school supervisor are expected to all lead to improving the quality of the school and education in general, and specifically supervision aimed at improving the quality of the school in terms of management is called managerial supervision. This is certainly no less important than academic supervision whose targets are teachers and learning. Without good school management, a climate would not be created that would allow teachers to work well. Therefore this paper will discuss and recognize several managerial supervision methods